The Engaging Interactive Kahoot Application for Vocabulary Mastery and Students’ Motivation - Devitriana, Annisa; Wijirahayu, Suciana (Journal of English Teaching, Literature, and Applied Linguistics, 2025)
This study investigates the influence of Kahoot, a game-based learning platform, in enhancing vocabulary mastery and learning motivation among tenth-grade students in Depok, Indonesia. The research addresses the challenges faced by students in vocabulary acquisition, particularly in Narrative and Recount texts. Through a descriptive qualitative approach and utilizing cluster purposive sampling, this study examines how Kahoot's interactive features facilitate vocabulary learning and boost student engagement. The research design is a survey, which was conducted at a private senior high school in Depok (West Java), involving a total of 72 student as participants. Data collection involved questionnaires with Likert scales, open-ended questions, and vocabulary tests administered among tenth-grade students. Findings revealed that Kahoot successfully transformed traditional vocabulary learning into an engaging educational experience through its gamified approach and user-friendly interface. The platform's immediate feedback mechanisms and competitive elements fostered active participation while facilitating vocabulary retention. However, technical challenges such as internet connectivity issues and competitive pressure occasionally hindered the learning experience. Despite these limitations, the study demonstrates that Kahoot effectively balances educational content with entertainment, leading to improved vocabulary retention and increased student motivation.